Great writing. 1, Great sentences for great paragraphs - Folse, Keith S.; Muchmore-Vokoun, April; Vestri, Elena (2020)
The new edition of the Great Writing series provides clear explanations, extensive models of academic writing and practice to help learners write great sentences, paragraphs, and essays. With expanded vocabulary instruction, sentence-level practice, and National Geographic content to spark ideas, students have the tools they need to become confident writers. Updated in this Edition: Clearly organized units offer the practice students need to become effective independent writers. Each unit includes: Part 1: Elements of Great Writing teaches the fundamentals of organized writing, accurate grammar, and precise mechanics. Part 2: Building Better Vocabulary provides practice with carefully-selected, level-appropriate academic words. Part 3: Building Better Sentences helps writers develop longer and more complex sentences. Part 4: Writing activities allow students to apply what they have learned by guiding them through writing, editing, and revising. Part 5: New Test Prep section gives a test-taking tip and timed task to prepare for high-stakes standardized tests, including IELTs and TOEFL. The new guided online writing activity takes students through the entire writing process with clear models for reference each step of the way.
Unit 1. Sentence basics -- Unit 2. Paragraph basics -- Unit 3. Writing about the present -- Unit 4. Writing about the past -- Unit 5. Writing about the future -- Unit 6. Sentence variety -- Unit 7. Reader response -- Unit 8. Putting it together.
Includes index.
Keywords: English language -- Sentences -- Problems, exercises, etc; English language -- Paragraphs -- Problems, exercises, etc; English language -- Rhetoric -- Problems, exercises, etc; English language -- Grammar -- Problems, exercises, etc; Report writing -- Problems, exercises, etc; English language -- Grammar; English language -- Paragraphs; English language -- Rhetoric; English language -- Sentences; Report writing; Problems and exercises